2017
DOI: 10.1177/0300060517708945
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous dexmedetomidine during spinal anaesthesia for caesarean section: A meta-analysis of randomized trials

Abstract: ObjectiveTo evaluate the efficacy and safety of spinal anaesthesia using dexmedetomidine for caesarean section.MethodsPubMed, The Cochrane Library, and CNKI were searched for relevant literature.ResultsThe incidence of nausea and vomiting in the dexmedetomidine group was significantly lower than that in the control group (OR = 0.21, 95% CI: 0.12–0.35, P < 0.00001). No difference was found in the incidence of pruritus between the two groups (OR = 1.21, 95% CI: 0.36–4.09, P = 0.76).The dexmedetomidine group had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
15
1
2
Order By: Relevance
“… 29 The reasons for shivering may include suppression of spinal reflex activity, decrease in sympathetic activity, and inhibition of adrenal function. 30 Many studies reported that DEX could effectively reduce the incidence of shivering during neuraxial anesthesia in patients undergoing cesarean section, without any associated respiratory depression as with other antishivering drugs, such as meperidine. 18 22 The present meta-analysis showed the same results reported in previous clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 The reasons for shivering may include suppression of spinal reflex activity, decrease in sympathetic activity, and inhibition of adrenal function. 30 Many studies reported that DEX could effectively reduce the incidence of shivering during neuraxial anesthesia in patients undergoing cesarean section, without any associated respiratory depression as with other antishivering drugs, such as meperidine. 18 22 The present meta-analysis showed the same results reported in previous clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the usage of DEX could reduce the demand for opioids during cesarean section. 18 , 19 , 30 This means that DEX may not only increase the incidence of PONV but also reduce the incidence of PONV during cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Use of DEX in cesarean section anesthesia has received more and more attention. Studies have shown that DEX can be used as an auxiliary for general anesthesia and intrathecal anesthesia in cesarean section; it can enhance the anesthetic effects, prevent and reduce adverse reactions of anesthetics, and reduce the amount of anesthetic drugs used [14][15][16]. However, when DEX is used in cesarean section to improve anesthesia, there are concerns about whether DEX will adversely affect the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…The Food and Drug Administration (FDA) has approved dexmedetomidine for limited use for sedation, mechanical ventilation and monitored anesthesia care in adults (3). There are current reports on the intraoperative use of dexmedetomidine for various indications including Cesarean sections (4)(5)(6)(7)(8). It is crucial to elucidate the possible effects of dexmedetomidine on the uterus and fetal circulation.…”
Section: Introductionmentioning
confidence: 99%